Pulmonary embolism as uncommon presentation for primary antiphospholipid syndrome in young male - Ruslan, Mohamad Azhari; Jamhuri, Nur Syazwani; Ibrahim, Ismail (Malaysian Society of Pathologists, 2024)
Introduction: Antiphospholipid syndrome (APS) is an autoimmune disease and it is uncommon in paediatric population with even gender distribution. Primary APS (PAPS) occurs in isolation with commonest presentation of arterial thrombosis, in contrast to venous thrombosis in secondary APS (SAPS). Systemic lupus erythematosus (SLE) is frequently associated with SAPS. Here is a case of 15-year-old boy, presented with pulmonary embolism which led to the diagnosis of primary APS. Case report: An active 15-year-old boy presented with acute exertional dyspnoea. He was hypoxic, requiring oxygenation support. Computed tomography (CT) thorax shows extensive bilateral pulmonary embolism. Coagulation profile revealed isolated prolong activated partial thrombin time (aPTT). Mixing study indicated presence of coagulation inhibitor. APS diagnosis made by presence of triple positivity of antiphospholipid antibodies. Autoimmune disease screenings were negative except for positive p-antineutrophilic cytoplasmic antibody (p-ANCA), without clinical evidence of vasculitis. His final diagnosis is primary APS with pulmonary embolism and currently treated with warfarin. Discussion: Antiphospholipid syndrome is uncommon in paediatric population. In contrast to adult APS, gender distribution is even and for PAPS, common manifestation is arterial thrombosis compared to venous thrombosis in SAPS. Based on largest paediatric APS registry, commonest venous thromboembolism is deep vein thrombosis (DVT). Pulmonary embolism in context of PAPS is an unusual presentation. High index of suspicion is crucial in children presenting with thrombotic events with no risk factor. Follow-up care is important as few cases of PAPS diagnosis are revised to SAPS with subsequent diagnosis of SLE.